2010
DOI: 10.1093/aje/kwq131
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Endogenous Reproductive Hormones on F2-Isoprostane Levels in Premenopausal Women: The BioCycle Study

Abstract: Endogenous reproductive hormones and oxidative stress have been independently linked to risk of chronic disease but mostly in postmenopausal women. The interplay between endogenous reproductive hormones and oxidative stress among premenopausal women, however, has yet to be clearly elucidated. The objective of this study was to investigate the association between endogenous reproductive hormones and F(2)-isoprostanes in the BioCycle Study. Women aged 18-44 years from western New York State were followed prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 40 publications
3
49
0
1
Order By: Relevance
“…Details of the study design and sample collection are described elsewhere (15). In brief, the BioCycle Study was designed to determine the association of oxidative stress levels with endogenous reproductive hormone and antioxidant concentrations across the menstrual cycle in a prospective cohort of premenopausal women (15)(16)(17). The study prospectively recruited 259 healthy, regularly menstruating women with self-reported cycle lengths of 21-35 d for $6 mo before recruitment from western New York in [2005][2006][2007].…”
Section: Methodsmentioning
confidence: 99%
“…Details of the study design and sample collection are described elsewhere (15). In brief, the BioCycle Study was designed to determine the association of oxidative stress levels with endogenous reproductive hormone and antioxidant concentrations across the menstrual cycle in a prospective cohort of premenopausal women (15)(16)(17). The study prospectively recruited 259 healthy, regularly menstruating women with self-reported cycle lengths of 21-35 d for $6 mo before recruitment from western New York in [2005][2006][2007].…”
Section: Methodsmentioning
confidence: 99%
“…A potential interplay between endogenous sexual hormones (including E2, sex hormonebinding globulin, follicle stimulating hormones, etc.) and F2-iso, as reliably measured by GS-MS, was also prospectively investigated in BioCycle Study, a cohort investigation on 259 women aged 18-44 years followed for two menstrual cycles [123]. F2-iso displayed positive independent association with circulating E2 levels throughout the menstrual cycle.…”
Section: Methodology Shortcomingsmentioning
confidence: 99%
“…The BioCycle study was designed to investigate oxidative stress levels across the menstrual cycle in healthy women age 18–44 [13] who were followed for one ( n = 9) or two menstrual cycles ( n = 250). The study design, procedures, and participants have been described in detail elsewhere [14].…”
Section: Methodsmentioning
confidence: 99%